Biological Markers of Mesenchymal Stromal Cells as Predictors of Response to Autologous Stem Cell Transplantation in Patients With Amyotrophic Lateral Sclerosis: An Investigator-Initiated Trial and In Vivo Study. (15th September 2014) - Kim, Hyun Young; Kim, Heejaung; Oh, Ki-Wook; Oh, Seong-Il; Koh, Seong-Ho; Baik, Wonki; Noh, Min Young; Kim, Kyung Suk; Kim, Seung Hyun
Abstract: Bone marrow mesenchymal stromal cells (MSCs) can modify disease progression in amyotrophic lateral sclerosis (ALS) model. However, there are currently no accurate biological markers for predicting the efficacy of autologous MSC transplants in ALS patients. This open-label, single-arm, investigator-initiated clinical study was designed to identify markers of MSCs that could be used as potential predictors of response to autologous MSC therapy in patients with ALS. We enrolled 37 patients with ALS who received autologous MSCs via intrathecal injection in two monthly doses. After a 6-month follow-up period, the patients were categorized as responders and non-responders based on their scores on the revised ALS Functional Rating Scale (ALSFRS-R). Biological markers including β-fibroblast growth factor-2, stromal cell-derived factor-1α, vascular endothelial growth factor (VEGF), insulin-like growth factor-1, brain-derived neurotrophic factor, angiogenin (ANG), interleukin (IL)−4, IL-10, and transforming growth factor-β (TGF-β) were measured in the MSC cultures and their levels were compared between the responders and nonresponders. To confirm the markers' predictive ability, MSCs isolated from one patient in each group were transplanted into the cisterna magna of mutant SOD1 G93A transgenic mice to measure their lifespans, locomotor activity, and motor neuron numbers. The levels of VEGF, ANG, and TGF-β were significantly higher in responders than in nonresponders. In the mouse model, the recipients of responder MSCs had a significantly slower onset of symptoms and a significantly longer lifespan than the recipients of nonresponders or controls. Our data suggest that VEGF, ANG, and TGF-β levels in MSCs could be used as potential biological markers to predict the effectiveness of autologous MSC therapy and to identify those patients who could optimally benefit from MSC treatment. Stem Cells   2014;32:2724–2731